Diagnostic assessment of product lifecycle management based on Industry 4.0 requirements - Kássio Cabral Pereira dos Santos; Eduardo de Freitas Rocha Loures; Osiris Canciglieri Junior; André Luiz Micosky (Production)
Abstract Paper aims Diagnostic analysis of PLM (Product Lifecycle Management) based on Industry 4.0 requirements supported by the AHP (Analytic Hierarchy Process) method. Originality The literature review found no research papers on PLM Maturity Models linked to requirements of Industry 4.0, attesting to the originality of the research and the topic proposed by the study. Research method The analysis is performed using an assessment framework that organizes and lists I4.0 attributes and PLM categories, supported by a multicriteria diagnostic assessment model based on the AHP method. The case study used in the research is an automotive industry located in the city of Curitiba, Brazil. Main findings A diagnostic analysis of the PLM categories and attributes of the I4.0 was performed, and the company’s overall levels of maturity were observed. Implication for theory and practice The results obtained from the diagnostic analysis indicate that the company maturity is Level 2, analyses were also undertaken with respect to PLM categories and Industry 4.0 attributes. Proposals for improvements were made with the objective of increasing the level of maturity and reducing gaps and problems identified in the diagnostic assessment.